Dietary health clubs for ethnic minority women in Northern Vietnam improved diet quality through vegetable and nutrition capacity building and seed access. - Swaans, Cornelis P.M.; Nabuuma, Deborah (2023)
Dietary health clubs were formed as a platform for creating awareness and exchanging information and skills on vegetables (seeds, production) and nutrition to enhance demand for and utilization of diverse vegetables and quality seeds. The club facilitators have increased their agency as change agents and sources of information in the villages. There was an increase in ethnic minority women members’ access to information, improved knowledge and skills, and enhanced household vegetable availability and consumption and dietary diversity. This is contributing to household nutrition security.